Comparison of 66 chemical element contents in normal and benign hyperplastic prostate - Vladimir Zaichick; Sofia Zaichick (Asian Journal of Urology)
Objective: The aim of this study was to clarify the differences between the prostatic levels of chemical elements in patients with benign prostatic hyperplasia (BPH) and healthy male. Methods: We evaluated the prostatic level of 66 chemical elements in 43 patients with BPH and 37 healthy males. Measurements were performed using five instrumental analytical methods. Results: In the hyperplastic prostates, we have observed a significant increase in the mean level of Bi, Cr, Hg, K, Sb, and Se accompanied a significant decrease in the mean level of Al, Ce, Cs, Dy, Er, Gd, Ho, La, Mo, Nd, Pb, Pr, Sm, Sn, Tb, Tm, U, and Y. No differences were found in the mean prostatic level of other chemical elements including Ag, Al, Au, B, Ba, Be, Br, Ca, Cd, Co, Cu, Fe, Li, Mg, Mn, Na, Nb, Ni, P, Rb, S, Sc, Si, Th, Ti, Tl, Yb, Zn, and Zr between BPH patients and healthy males. Conclusions: The finding of chemical element contents and correlation between pairs of chemical element mass fractions indicates that there is a great disturbance of prostatic chemical element metabolism in BPH gland. Trace elements Bi, Cr, Hg, K, Sb, and Se may be regarded as the possible tissue biomarkers of hyperplastic transformation of prostate gland. Obtained data did not confirm a critical role of Cd and Pb accumulation in the pathogenesis of BPH. A potential age-related Zn, Fe, and Se deficiency in the prostate tissue has not been found as being involved in the etiology of BPH. Keywords: Benign prostate hyperplasia, Prostatic chemical element contents, Trace element supplementations, Energy dispersive X-ray fluorescence analysis, Neutron activation analysis, Inductively coupled plasma atomic emission and mass spectrometry